1986
DOI: 10.1111/j.1540-6288.1986.tb01120.x
|View full text |Cite
|
Sign up to set email alerts
|

Liquidity and Price Variability in Futures Markets

Abstract: This paper tests the hypothesis that market liquidity affects the price variability of futures contracts. The analyses used take into account the maturity effect and various sources of nonstationarity. Empirical testing involved eleven commodities in various markets. The evidence strongly suggests that futures contracts in distant and thinly traded months exhibit different price variability than contracts in near to maturity and liquid traded months, and that the behavior is commodity dependent. These findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…The objective of this article is to draw attention to the validity of the assumption of constant variance of the underlying futures price within the framework of an options pricing model. Furthermore, we aim to improve on current aproaches in this area by utilizing recent evidence in futures markets.Recent evidence which appeared in this Journal (Castelino and Francis, 1982;Anderson, 1985;and Milonas, 1986a) and elsewhere (Castelino, 1981 andMilonas, 1986b) strongly supports Samuelson's (1965) maturity effect hypothesis (futures variance increases as maturity nears) for a wide range of agricultural, metals and financial futures contracts. The agreement of the above studies on the maturity effect is due to the use of a large number of observations and to an improved methodology over previous methodologies which presented mixed results (Miller, 1979 andRutledge, 1976).…”
supporting
confidence: 69%
See 1 more Smart Citation
“…The objective of this article is to draw attention to the validity of the assumption of constant variance of the underlying futures price within the framework of an options pricing model. Furthermore, we aim to improve on current aproaches in this area by utilizing recent evidence in futures markets.Recent evidence which appeared in this Journal (Castelino and Francis, 1982;Anderson, 1985;and Milonas, 1986a) and elsewhere (Castelino, 1981 andMilonas, 1986b) strongly supports Samuelson's (1965) maturity effect hypothesis (futures variance increases as maturity nears) for a wide range of agricultural, metals and financial futures contracts. The agreement of the above studies on the maturity effect is due to the use of a large number of observations and to an improved methodology over previous methodologies which presented mixed results (Miller, 1979 andRutledge, 1976).…”
supporting
confidence: 69%
“…The agreement of the above studies on the maturity effect is due to the use of a large number of observations and to an improved methodology over previous methodologies which presented mixed results (Miller, 1979 andRutledge, 1976). The new methodology attempted either to control for nonstationarity sources such as the "year effect", "month effect" or "contract month effect" (Castelino, 1981and Milonas, 1986a, 1986b; or to explicitly capture the seasonal factors (Anderson, 1985). Direct measurement of the above nonstationarities was given by Milonas and Vora (1985), whose study also suggested that the incorporation of the above nonstationarities in methodologies dealing with futures prices is required in order to avoid serious biases.Hauser and Neff (1985), use agricultural options as an example in which direct…”
mentioning
confidence: 92%
“…The specific definitions and units of measure for the variables are given in Table I for the 1976-1986 sample period. 'The variance of the change in log prices is used by many authors exploring volatility [Anderson (1984); Kenyon et al (1987);Milonas (1984); Glauber and Heifner (1986); Brorsen and Irwin (1987); Brorsen (1989)l. If futures prices are a random walk in log prices, then the dependent variable is an estimate of the variance of the random error of the series, a conditional variance.…”
Section: The General Modelmentioning
confidence: 99%
“…With little change in information, a reduction in price volatility might be expected. Although previous studies find evidence supporting the Samuelson hypothesis in soybean markets [Anderson (1985); Milonas (1984)], this study seeks to explore whether that effect holds up when a more complete model is specified.…”
Section: Flow and Certainty Of Information Variablesmentioning
confidence: 99%
“…Hong () shows that open interest can take on rich time‐to‐maturity patterns, based on the fact that the higher the adverse selection cost taken by uninformed investors, when they trade with informed investors, the lower the open interest will be. Milonas () examines the time‐to‐maturity pattern of open interest for different futures markets and finds that the very distant and nearest contracts have the least open interest, probably due to their high illiquidity. Further, the author finds that for the liquid contracts of intermediate maturities, different time‐to‐maturity patterns can also arise, with more distant contracts having more or less open interest than those nearer to the expiration.…”
mentioning
confidence: 99%